Strain-rate dependence of the brittle-to-ductile transition temperature in tungsten - Giannattasio, A; Roberts, S (2007)
We have investigated the strain-rate dependence of the brittle-to-ductile transition (BDT) temperature in pre-cracked tungsten single-crystals and polycrystals. There is an unambiguous Arrhenius relationship over four decades of strain rate, giving an activation energy for the process controlling the BDT of 1.05 eV. This is equal to the activation energy for double-kink formation on screw dislocations, suggesting that their motion controls the brittle-ductile transition.